Sittig's handbook of pesticides and agricultural chemicals - Greene, Stanley A.; Pohanish, Richard P. (William Andrew Pub., 2005)
Sittig's Handbook of Pesticides and Agricultural Chemicals is specifically designed for use by those engaged in the agricultural and food processing industries, both vital to our nation's health and economy. People in every phase of food production, from the farm to the fork, will find a wealth of material here. It will also be of interest to professionals in the pharmaceutical, cosmetics, and personal care industries who use agricultural products as ingredients. It provides crop, chemical, regulatory, health and safety information on nearly 800 pesticides, fertilizers, and other agricultural chemicals. These chemicals are organized withg unique identifiers so that all who may have contact with or interest in them can find critical information quickly.
Companion volume to Sittig's handbook of toxic and hazardous chemicals and carcinogens.
Keywords: Pesticides -- Handbooks, manuals, etc.; Pesticides -- Environmental aspects -- Handbooks, manuals, etc.; Agricultural chemicals -- Handbooks, manuals, etc.; Agricultural chemicals -- Environmental aspects -- Handbooks, manuals, etc.; elektronické knihy; electronic books